Ethical Issues in Neuroscience and Neuropsychiatric: A Review of Major Issues - Adji Suwandono; Graffico Eryza Oldiara; Fitri Pranita Milyarona (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Adherence to ethical principles is essential nowadays in neuroscience and neuropsychiatric research. observance of ethical principles is essential in the case of neurology and neuroscience research, as it is in all the other medical and surgical fields. as neuroscience research advances, researchers, clinicians, and other stakeholders will face a host of ethical challenges. Ethical problems of neuroscience-based diagnosis and interventions. This section concerns problems resulting from neuroimaging, pharmacological brain enhancement, and new technical interventions in the brain. The research is based on a literature review, so data will be collected from literary sources such as scientific journals, books, and articles in January 2023 relating to the research topic. The literature search process must be systematically documented, including keywords, databases used, and search dates. Data analysis will be carried out by reading and understanding the content of the literature, identifying ethical problems encountered in the field of neuroscience and neuropsychiatry, and analyzing different perspectives in addressing these ethical problems. In this article, we also review the major ethical issues raised by advances in neuropsychiatric genetics. Advances in neuroscience raise ethical, social, and legal issues about the human person and the brain. The potential benefits of applying neuroimaging, psychopharmacology, and neurotechnology to support mentally ill and healthy persons have to be carefully weighed against their potential harm. Questions concerning underlying concepts of humans should be actively dealt with by interdisciplinary and public debate. t is therefore essential to develop bioethics and encourage discoveries in neuroscience to firmly respect the ethical principles available at the time of their publication.Keyword: Ethical Issues, Neuroscience, Neuropsychiatric